Le mouvement de conservation des ressources naturelles pendant l’ère progressiste : la stratégie et la vision de Theodore Roosevelt - Wiley, Patrick (Université de Montréal, 2020)
Theodore Roosevelt's term in the White House (1901-1909) was marked by many efforts in the conservation of natural resources. This was a doubly important theme for Roosevelt, because not only did he see the negative effects of industrialization on the future of resources, but nature had been one of his passions since his childhood. Thus, he wanted to continue to father a conservationist movement that had existed since the 1870s. Ultimately, his objective was to consolidate all natural resources under the authority of the federal government, through numerous policies for the development of forests, agricultural lands, rivers, pastures, ranges and mineral lands. This thesis presents the many perspectives from which conservation developed under Roosevelt, as well as the role of important individuals in the conservation community during the Roosevelt era. Although conservation is generally associated with the economic benefits of natural resources and their actual uses, we explore what other issues conservation could address. Theodore Roosevelt was very attached to his idea of a typically American nation and to what he saw as the essential values of the United States. Thus, we examine the link that might have existed between this ideal of the nation and the efforts to protect natural resources. Our study shows that, by putting his conservation project into practice, Roosevelt was able to remain true to some of the ideals he believed were essential to the proper functioning of American society.
Keywords: History - United States / Histoire - États-Unis (UMI : 0337); Theodore Roosevelt; Unites States; conservation; nation; natural resources; progressive era; ressources naturelles; valeurs; values; États-Unis; ère progressiste

Mille après mille : mobilité, célébrité et mémoire des artistes populaires après «l'exode» - Lavoie, Pierre (Université de Montréal, 2020)
Art history and cultural history in Quebec present many examples of “retours d’Europe” and of “French triumphs,” from the formative overseas stays of the “exotiques” in the 1910s to the stage success of Quebec “chansonniers” in Paris in the 1950s and 1960s. However, between the early 1930s and the mid-1950s, some of the most famous French-speaking artists based in Montréal preferred to go on tour in the United States. Many of them traveled New England year after year, sometimes going as far as New York City, to cheer the French-speaking public present along the way in the industrial cities of the region. Yet this episode of high mobility is almost absent from history, memory and cultural heritage in Quebec—and even more so in the United States. Beyond the impact of the Great Depression on Montréal’s cultural scene and of the Second World War on the possibility of visiting Europe, these artists have turned their eyes towards America because they participated in a transnational space, both geographical and symbolic, inherited from an era of great intracontinental migrations, then reactivated and reconfigured by the advent of sound and audiovisual media—discs, radio and cinema. By studying the history of the celebrity of Mary “La Bolduc” Travers, Rudy Vallée and Jean Grimaldi, this thesis attempts to access to the various layers of this phenomenon at the crossroads of cultural history, media history and migration history. Their intricate narratives therefore reveal the modality of mobility involved inside—and often times outside—of the French Canadian “imagined community.” By analyzing the heritagization process of these artists, it is possible to isolate some of the causes the oblivion of this transnational episode of francophone culture in North America, such as the rejection of mobility in the formation of national and ethnic identity narratives; the historical marginalization of popular arts; and the mistrust of the United States among cultural and political elites around the world at the time.
Keywords: 20e siècle; 20th century; History - Canadian / Histoire - Canadienne (UMI : 0334); New England; Nouvelle-Angleterre; Quebec; Québec; art populaire; celebrity; collective identification; célébrité; heritagization; identification collective; media; migration; mobility; mobilité; médias; mémoire publique; patrimonialisation; popular art; public memory; tour; tournée